1977
DOI: 10.1021/jf60210a022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the protein compositions of selected corns and their wild relatives, teosinte and Tripsacum

Abstract: To establish evolutionary and genetic relationships,, the proteins of a hybrid field corn, an Illinois high-protein corn, and an Argentine popcorn were compared to those of two wild relatives, teosinte and Tripsacum. After sequential extractions of grain meals by a modified Osborne-Mendel scheme, the protein classes obtained were subjected to amino acid analyses and electrophoresis in various systems. Tripsacum yielded less zein and more alcohol-soluble reduced glutelin than the other grains. These differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
40
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 10 publications
8
40
0
Order By: Relevance
“…1). Our results are consistent with those of Paulis and Wall (1977), where they found protein levels of 28.7% in their parviglumis teosinte accession. The protein content of teosinte was almost as high as protein levels obtained by the Illinois Long-Term Selection Experiment (Dudley 2007) without a corresponding change in the embryo to endosperm ratio (Bjarnason and Pollmer 1972).…”
Section: Kernel Composition and Seed Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…1). Our results are consistent with those of Paulis and Wall (1977), where they found protein levels of 28.7% in their parviglumis teosinte accession. The protein content of teosinte was almost as high as protein levels obtained by the Illinois Long-Term Selection Experiment (Dudley 2007) without a corresponding change in the embryo to endosperm ratio (Bjarnason and Pollmer 1972).…”
Section: Kernel Composition and Seed Characteristicssupporting
confidence: 92%
“…The essential amino acids lysine, tryptophan, and methionine are limited because they are lacking or present at low levels in zeins, the major class of storage proteins. Zeins constitute about half of the endosperm protein, and thus nearly half of the total seed protein (Paulis and Wall 1977). Genetic and genomic studies have revealed great complexity of zein gene families (Song et al 2001;Song and Messing 2002;Wilson and Larkins 1984;Woo et al 2001) and support earlier observations that diVerent classes of zeins have varying amino acid compositions (Melcher and Fraij 1980;Sodek and Wilson 1971).…”
Section: Introductionsupporting
confidence: 57%
“…This hypothesis has been confirmed by electrophoresis in urea gels (19,21), gel filtration in the presence of urea (19), and SDS-PAGE2 (18,20). The zein II fraction contains all of the polypeptides of the zein I fraction, but in addition contains two or more polypeptides of greater cathodal mobility at pH 2.9 (21) and lower mol wt (18,20) than the zein I fraction polypeptides. Amino acid analyses of the low mol wt fractions from gel filtration confirmed the high methionine content of the smaller polypeptides (19).…”
mentioning
confidence: 88%
“…Zein II contains onefourth to one-half the amount of protein in zein I (7,21 I protein with 10 to 20o of a protein fraction rich in methionine and glycine and deficient in leucine, isoleucine, phenylalanine and aspartic acid and/or its amide (7,21). This hypothesis has been confirmed by electrophoresis in urea gels (19,21), gel filtration in the presence of urea (19), and SDS-PAGE2 (18,20). The zein II fraction contains all of the polypeptides of the zein I fraction, but in addition contains two or more polypeptides of greater cathodal mobility at pH 2.9 (21) and lower mol wt (18,20) than the zein I fraction polypeptides.…”
mentioning
confidence: 89%
“…The presumed ancestral forms and evolutionary patterns of chickpea [49], maize [50], wheat [51] and soybean [52,53] have been identified and established by studying the electrophoretic variability of their respective seed proteins. Gepts [54] used phaseolin as an evolutionary marker in his insightful review of the domestication pattern and world-wide dispersal of the French bean.…”
Section: Phaseolin Polypeptides As Evolutionary Markers -French Bean mentioning
confidence: 99%